Length-Weight Relationship and Condition Factor of Yellowfin Tuna (Thunnus albacares) from Demta Coast, Jayapura Regency, Papua - Kalor, John Dominggus; Paiki, Kalvin; Rumahorbo, Basa T. (Hasanuddin University, 2022)
The population of Thunnus albacares yellowfin tuna from the Scombridae family is very abundant in North Papua Waters (WPP 717). This study aims to analyze the parameters of population dynamics based on the long-weight relationship and condition factors on Thunnus albacares in Demta Coastal Waters, Jayapura Regency. Fish data collection uses passive and active fishing methods using gill nets, handlines, and long line fishing through fishing activities by traditional fishermen during April - June 2022. Data analysis uses analysis length-weight relationship and condition factor. The results of this study found that the population structure of yellowfin tuna (T. albaceras) was very diverse in the waters of North Papua, with a negative allometric growth pattern (b < 3), i.e. the growth of body length was faster than weight. The condition factor averaged 1.1302 with a maximum of 1.4718 and a minimum of 0.7028. Where in the gonadal maturity period morphometric adaptation occurs, weight growth becomes faster and body length becomes slower.